Spectrophotometric and potentiometric investigation of vanadium(V) oxyion equilibria - Westra, Arjan N.(Arjan Nicolaas) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1993.